(untitled) (Ascendens Asia Singapore – Union Christian College Philippines Journal of Multidisciplinary Research Abstracts, 2020)
Teachers face ongoing challenges to balance sensitivity to the social and learning needs of the community they serve with pressures to meet broader labor market, social, and political objectives. Their day-to-day encounters in their profession embody their significant role in bringing educational services to the neediest of these. This study explored the lived experiences of teachers in the last-mile schools in Santol District in the La Union Schools Division as a basis for a revitalized teachers’ orientation program. The researcher employed the sequential exploratory research design, particularly the hermeneutic phenomenological analysis and descriptive-correlation approach, to triangulate analysis of the data gathered. The researcher analyzed the qualitative data from the selected teachers in Santol, La Union, using thematic analysis and quantitative data using descriptive and inferential statistics. The study found that the experiences of teachers deployed in the last-mile schools highlighted both rewarding and frustrating encounters that tested their commitment to their profession. Additionally, these are a rich source of inputs to further the orientation program of the Department of Education of their teachers in various social settings. Moreover, the age, employment status, and exposure to various language backgrounds of the respondents were of significant associations in their deployment to the last-mile schools; and their experiences of the respondents are highly correlated to their sense of rewards as teachers. In this view, the researcher concluded that the orientation of teachers to the last-mile schools needs consideration of the teacher’s background and baseline inputs from their predecessors; hence, the adoption of the revitalized teachers’ orientation program is strongly endorsed.